2010
DOI: 10.1080/10401334.2010.488191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Empathy Among Korean Medical Students: A Cross-Sectional Study Using the Korean Version of the Jefferson Scale of Physician Empathy

Abstract: Our findings provide support for the reliability and validity of the Korean JSPE-S and indicate that it can serve as a useful instrument for assessing empathy among Korean medical students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
138
11
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(194 citation statements)
references
References 15 publications
35
138
11
10
Order By: Relevance
“…The mean empathy score among the medical students in KAU was 106.55 and this level seems to be relatively lower than what was reported in some Western countries such as the USA, mean score was 115, [15,13] and German, mean score was 110.52 [14]. However, the mean score of empathy level of our KAU medical students was near to that of the Asian medical students such as in Iran, mean score was 105.1 [7], in Kuwait, mean score was 104.6 [10], Japan, mean score was 104.3 [4], and Korea, mean score was104 [5]. Cultural and social issues could be behind these variations between western and eastern countries.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The mean empathy score among the medical students in KAU was 106.55 and this level seems to be relatively lower than what was reported in some Western countries such as the USA, mean score was 115, [15,13] and German, mean score was 110.52 [14]. However, the mean score of empathy level of our KAU medical students was near to that of the Asian medical students such as in Iran, mean score was 105.1 [7], in Kuwait, mean score was 104.6 [10], Japan, mean score was 104.3 [4], and Korea, mean score was104 [5]. Cultural and social issues could be behind these variations between western and eastern countries.…”
Section: Discussionmentioning
confidence: 67%
“…Education and Health Careat Jefferson Medical College, to measure the level of empathy among physicians and other health professionals [3].The hypothesis that empathy declines as students' progress through medical school has previously investigated in many Asian countries like Japan [4], South Korea [5], China [6], Iran [7], Bangladesh [8] and India [9], some Arabic countries as Kuwait [10], as well as other countries like UK [11], USA [12], Brazil [13] and German [14] by using the student version of Jefferson Scale of Physician Empathy (JSPE). To our knowledge, the empathy with patients among the Saudi medical students has not been studied till now.…”
Section: The Jefferson Scale Of Empathy (Jse) Was Developed At the Cementioning
confidence: 99%
“…7 The curriculum in India differs from western countries in that clinical rotation starts from second year itself and from Korea and Japan in that there is no humanities content in the curriculum. 12,13 Studies have shown that medical students who plan to pursue people oriented specializations such as internal medicine, family medicine, psychiatry and pediatrics showed higher empathetic scores and across all years of study in medical school than those who choose to pursue technology oriented specialties such as radiology, surgery and anesthesiology 8,14 . These changes were reported more among male students and those selecting noncore subject such as other than internal medicine, family medicine, obstetrics and gynecology and psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…4,7,8,13 However a Japanese study found no decline in empathy scoring as students progressed from non-clinical to clinical training. 12 In view of such varying empathy findings from different countries, we need to understand empathy among medical students in Indian context. Do our female students have more empathy than male students?…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated 22 that there is gender variability in relation to empathy in a study in 18 dental schools in Latin America. As a consequence, it is not possible to state categorically that women are more empathetic than men in all populations studied, despite the fact that authors have observed the opposite [8,[23][24][25][26][27].…”
Section: General Empathymentioning
confidence: 79%